Fostering Celestial Curiosity: The SEAROAD Astronomy Workshop for the Professional Development of Indonesian Science Educators - Judhistira Aria Utama; Muhammad Zahran; Feri Apryandi; Cahyo Puji Asmoro; Winny Liliawati; M. Reza Dwi Saputra (Jurnal Pemberdayaan Masyarakat, 2025)
Community engagement in science is essential for building a knowledgeable and inspired society. This paper reports on the SEAROAD (Southeast Asia Regional Outreach Astronomy Development) Astronomy Workshop, a community service initiative designed to enhance science educators' understanding of astronomy and their confidence in teaching it. The two-day program in Bandung, West Java, involved 36 participants from diverse educational backgrounds. Pre-workshop assessments measured the baseline knowledge of participants on topics such as light pollution, telescope use, and celestial phenomena. At the same time, post-workshop surveys evaluated shifts in attitudes, perceived relevance, and interest in astronomy. Results revealed notable gaps in prior knowledge and demonstrated significant cognitive gains, with most participants achieving moderate to high normalized change scores. The workshop also strengthened pedagogical self-efficacy, particularly in integrating astronomy into classroom practice. This study presents one of the first systematic evaluations of an astronomy-focused teacher professional development intervention in Indonesia, implemented through a tripartite collaboration that combines local pedagogy, public science communication, and regional scientific partnerships. These findings highlight the effectiveness of short-term, hands-on, and contextually relevant professional development as a model for advancing science education and fostering sustained public interest in astronomy. Beyond its practical outcomes, this study contributes to the broader discourse on teacher professional development by offering an evidence-based framework for how collaborative, intensive, and contextually grounded astronomy training can effectively enhance both cognitive and affective domains of educators in developing countries.